Dosing Common Medications in Hospitalized Pediatric Patients with Obesity: A Review. Issue 6 (22nd May 2020) - Ameer, Barbara; Weintraub, Michael A.
Abstract : Medication management in children and adolescents with obesity is challenging because both developmental and pathophysiological changes may impact drug disposition and response. Evidence to date indicates an effect of obesity on drug disposition for certain drugs used in this population. This work identified published studies evaluating drug dosing, pharmacokinetics (PK), and effect in pediatric patients with obesity, focusing on 70 common medications used in a pediatric network of 42 US medical centers. A PubMed search revealed 33 studies providing PK and/or effectiveness data for 23% (16 of 70) of medications, 44% of which have just one study and can be considered exploratory. This work appraising 4 decades of literature shows several promising approaches: greater use of PK models applied to prospective clinical studies, dosing recommendations derived from both PK and safety, and multiyear effectiveness data on drugs for chronic conditions (e.g., asthma). Most studies make dose recommendations but are weakened by retrospective study design, small study populations, and no controls or historic controls. Dosing decisions continue to rely on extrapolating knowledge, including targeting systemic drug exposure typically achieved in adults. Optimal weight‐based dosing strategies vary by drug and warrant prospective, controlled studies incorporating PK and modeling and simulation to complement clinical assessment.